Dual Harnessing of Air Conditioning Exhaust: PV Cooling and Dishwasher Drying - Charbel Habchi; Fadl Moukalled; Mahmoud Khaled (Energy and Built Environment)
This paper investigates the potential of utilizing air-conditioning (AC) system exhaust to cool Photo Voltaic (PV) panels, leading to improved efficiency. Additionally, the study explores harnessing the heat emitted from the PV modules for thermal applications. Numerical simulations demonstrate that this cooling method can enhance PV module efficiency by 5% to 50% compared to non-cooled scenarios. Moreover, the recovered hot air leaving the PV panels is directed to a dishwasher for drying purpose, thereby optimizing the overall energy utilization of the proposed system. An energetic and exergetic analysis of the recuperated thermal energy showcases its exceptional thermal efficiency, ranging from 98% to 45%, which aligns with values reported in existing literature. The exergetic efficiency of the suggested system falls between 5.2% and 1%, consistent with the range of values documented in previous studies. By exploiting AC system exhaust and waste heat, this new approach can significantly enhance the performance of PV panels and promote energy efficiency. Implementing this technology could prove instrumental in sustainable energy applications.